Biomimetic membrane platform : fabrication, characterization and applications - Bo, Liedberg (2013)
A facile method for assembly of biomimetic membranes serving as a platform for expression and insertion of membrane proteins is described. The membrane architecture was constructed in three steps: (i) assembly/printing of α-laminin peptide (P19) spacer on gold to separate solid support from the membrane architecture; (ii) covalent coupling of different lipid anchors to the P19 layer to serve as stabilizers of the inner leaflet during bilayer formation; (iii) lipid vesicle spreading to form a complete bilayer. Two different lipid membrane systems were examined and two different P19 architectures prepared by either self-assembly or μ-contact printing were tested and characterized using contact angle (CA) goniometry, surface plasmon resonance (SPR) spectroscopy and imaging surface plasmon resonance (iSPR). It is shown that surface coverage of cushion layer is significantly improved by μ-contact printing thereby facilitating bilayer formation as compared to self-assembly. To validate applicability of proposed methodology, incorporation of Cytochrome bo3 ubiquinol oxidase (Cyt-bo3) into biomimetic membrane was performed by in vitro expression technique which was further monitored by surface plasmon enhanced fluorescence spectroscopy (SPFS). The results showed that solid supported planar membranes, tethered by α-laminin peptide cushion layer, provide an attractive environment for membrane protein insertion and characterization.